2009
DOI: 10.1524/ract.2009.1585
|View full text |Cite
|
Sign up to set email alerts
|

Radiochemical analysis of a copper beam dump irradiated with high-energetic protons

Abstract: The radionuclide inventory of a copper beam dump from the 590 MeV proton accelerator of the Paul Scherrer Institute in Switzerland was determined, focusing on radioisotopes with half-lives of more than 60 d, and in particular, of long-lived isotopes with T 1/2 = 10 4 -10 7 years, which are important regarding radioactive waste management. The measurements were carried out using high resolution γ -measurement without sample destruction, as well as liquid scintillation counting (LSC) and accelerator mass spectro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 3 publications
0
41
0
Order By: Relevance
“…After an extended radiochemical analysis [7], the inner part of 2 cm, where the highest activity concentration of 26 Al, 44 Ti, 53 Mn, 60 Fe, 59 Ni and others was found, had been drilled out and is stored for further use.…”
Section: Targets and Beam Dumpsmentioning
confidence: 99%
“…After an extended radiochemical analysis [7], the inner part of 2 cm, where the highest activity concentration of 26 Al, 44 Ti, 53 Mn, 60 Fe, 59 Ni and others was found, had been drilled out and is stored for further use.…”
Section: Targets and Beam Dumpsmentioning
confidence: 99%
“…10 Be: After adding 2 mg of stable Be carrier, decomposition with aqua regia was used as described in [12]. Finally, the solution was evaporated to dryness and the residue dissolved in 1 M HNO 3 . This solution was fed onto a cation exchange column (DOWEX50x8, 200-400 mesh, H + -form).…”
Section: Chemical Treatmentmentioning
confidence: 99%
“…For PSI, that is operating the world-wide most powerful proton accelerator with up to 2.3 mA beam current and a beam energy of 590 MeV, it is mandatory to provide accurate data on the radionuclide inventory of its accelerator waste. While metallic components like stainless steel, cast iron, copper, aluminum and others are relatively frequently analyzed and evaluated [2,3], only one attempt was started some years ago to characterize a first set of con-*Author for correspondence (E-mail: dorothea.schumann@psi.ch).…”
Section: Introductionmentioning
confidence: 99%
“…The material that served for the separation of rare radionuclides is described in details elsewhere [5]. The expected radionuclide inventory of the collected copper sample (500 g) is listed in the Table 1 [5].…”
Section: Instrumentation and Reagentsmentioning
confidence: 99%
“…The results form the analytical procedures demonstrated that the cooper beam dump could serve as a valuable source for production of rare radionuclides such as 26 Al, 36 Cl, 32 Si, 59 Ni, 53 Mn, 44 Ti and 60 Fe. Therefore, based on the analytical results, a special research and development program has been started at PSI objecting on specific preparative extraction of long lived radioisotopes (ERAWAST-exotic radionuclides from accelerator waste for science and technology) [4,5].…”
Section: Introductionmentioning
confidence: 99%